Fair Value Accounting, Historical Cost Accounting, and Systemic Risk - Michael D. Greenberg, Eric Helland, Noreen Clancy, James N. Dertouzos (RAND Corporation, 2013)
Fair value accounting (FVA) refers to the practice of updating the valuation of assets or securities on a regular basis, ideally by reference to current prices for similar assets or securities established in the context of a liquid market. Fair value accounting is typically distinguished from historical cost accounting (HCA), which instead records the value of an asset as the price at which it was originally purchased. For decades, policymakers and professional experts have debated the relative merits of FVA and HCA and the quality of the information that each approach provides to investors and other key users of financial statements. In the wake of the 2008 financial crisis, conflicting arguments have been made about the contributions of valuation approaches in triggering the crisis. Critics have raised basic questions about the appropriateness of FVA methods, even as advocates pointed out that greater transparency in asset pricing and balance sheets ought to help protect against risk and speculative bubbles. The purpose of this report is to investigate and clarify the relationship between these two accounting approaches and systemic risk to the financial system. Specifically, the report examines the risk implications of FVA and HCA in the various situations in which each is used; assesses the role that these accounting approaches have played historically in financial crises, including the 2008 financial crisis, the savings and loan crisis of the 1980s, and the less developed country (LDC) debt crisis of the 1970s; and explores insights about systemic risk that can be gleaned from better understanding the accounting approaches. This study was funded with support from the Goldman Sachs Global Markets Institute, with additional support from the pooled resources of the RAND Center for Corporate Ethics and Governance. This report should be of interest to policymakers, regulators, financial services executives, accounting professionals and standard-setters, members of the business community, and other stakeholders with broad interests in accounting standards, valuation, risk management, systemic risk, and the global banking system.